Expression of Chemokine Genes in Human Dermal Microvascular Endothelial Cell Lines Infected with Orientia tsutsugamushi - Cho, Nam-Hyuk (American Society for Microbiology, 2001)
Scrub typhus, caused by Orientia tsutsugamushi, is characterized by local as well as systemic inflammatory manifestations. The main pathologic change is focal or disseminated multiorgan vasculitis, which is caused by the destruction of endothelial cells and perivascular infiltration of leukocytes. We investigated the regulation of chemokine induction in transformed human dermal microvascular endothelial cells (HMEC-1) in response to O. tsutsugamushi infection. The monocyte chemoattractant protein-1 (MCP-1) and interleukin 8 (IL-8) mRNAs were induced, and their levels showed a transitory peak at 3 and 6 h, respectively. The RANTES transcript was detected at 6 h after infection, with increased levels evident by 48 h. The induction of the MCP-1 and IL-8 genes was not blocked by cycloheximide, suggesting that de novo protein synthesis of host cell proteins is not required for their transcriptional activation. Heat- or UV-inactivated O. tsutsugamushi induced a similar extent of MCP-1 and IL-8 responses. The induction of MCP-1 and IL-8 transcripts in the endothelial cells by O. tsutsugamushi was not blocked by the inhibitors of NF-κB. Furthermore, the activation of NF-κB was not detected in HMEC-1 stimulated with O. tsutsugamushi. These results demonstrate that heat-stable molecules of O. tsutsugamushi induce the MCP-1 and IL-8 genes and the induction of the chemokine genes may be mediated by an NF-κB independent mechanism. We also showed that another major transcription factor, activator protein-1 (AP-1), was up-regulated in HMEC-1 after O. tsutsugamushi infection. This suggests the possible involvement of AP-1 in the chemokine gene expression.